Enhancing the reliability of six‐phase transmission line protection using power quality informatics with real‐time validation. (16th May 2019) - Shukla, Sunil K.; Koley, Ebha; Ghosh, Subhojit; Mohanta, Dusmanta K.
Summary: The increased power demand has motivated the use of a six‐phase transmission line. The acceptance of six‐phase transmission depends on the development of a comprehensive protection scheme. The relatively higher complexity of a six‐phase system, arising from the large number of possible faults, makes the protection task challenging. The intrusion of harmonics resulting from nonlinear loads further adds to the complexity. This paper proposes a data mining‐based protection scheme using power quality informatics of voltage signals for a six‐phase transmission line with nonlinear loading. The scheme has been extensively tested for evaluating its reliability in terms of accuracy, dependability, and security indices. Considering the stochastic nature of fault incidence, efficacy of the proposed approach has also been validated by Monte Carlo simulations. Further, to authenticate the proposed scheme for practical scenarios, implementation and validation of the proposed scheme have been carried out for real‐time environment using an OPAL‐RT digital simulator.